Conceptual Framework for Designing and Developing a Creativity Enhancement Module in Education Incorporating Indigenous Perspectives. - Chew, E. S.; Hamid, M. A.; Madar, A. R. (Pertanika Journal of Social Sciences & Humanities)
Creativity is rated among the most important human mental attributes or human capital that is considered by researchers as the driving force behind economic development, technical advances, work-place leadership and life success. As such, creativity is certainly an important aspect of technical and vocational education and training, in which design and innovation are among the core subjects. As the perspective that enhancement of creativity can be carried out through learning and training is accepted, the design and development of instructional modules plays a significant role in enhancing the creativity levels of both trainers and trainees, especially in the field of education. Teaching and learning resources in varying degrees of depth and difficulty that cater for the individual, groups and organizations can be prepared. This article sets forth a conceptual framework for a structure for a creativity enhancement module that includes its design, development and evaluation. Keys areas in the framework include theories of creativity and domains that are involved, theories of teaching and learning creativity, indigenous perspectives and theories of module design, development and evaluation of the module in the intervention process